Raza sí!, guerra no! : Chicano protest and patriotism during the Viet Nam war era - Oropeza, Lorena, 1964- (University of California Press, 2005)
This incisive and elegantly written examination of Chicano antiwar mobilization demonstrates how the pivotal experience of activism during the Viet Nam War era played itself out among Mexican Americans. Raza Sil Guerra No! presents an engaging portrait of Chicano protest and patriotism. On a deeper level, the book considers larger themes of American nationalism and citizenship and the role of minorities in the military service, themes that remain pertinent today. Lorena Oropeza's exploration of the evolution, political trajectory, and eventual implosion of the Chicano campaign against the war.